...........................
Запишем такое выражение.
На первой тарелке - Х
Тогда
Х + (Х+1) + [(Х+1)+1] = 24
Упрощаем
3*Х = 24 - 3 = 21
Находим Х
Х = 21 : 3 = 7 - на первой
7+1 = 8 - на второй
8+1 = 9 - на третьей
ОТВЕТ 7, 8 и 9 штук
1)7*4/37=(7*4)/37=28/37
2)8/13*4 1/3=8/13*13/3=(8*1)/(1*3)=8/3=2 2/3
3)7/15*3=(7*3)/15=(7*1)/5=7/5=1 2/5
4)3 3/8*7/9=(27*7)/(8*9)=(3*7)/(8*1)=21/8=2 5/8
5)4 4/17*3 7/18=(72*61)/(17*18)=(4*61)/(17*1)=244/17=14 6/17
7,2/2,4=х/51
2,4×Х=7,2×51
2,4х=367,2
х=367,2/2,4
х=153